Conditional Automaticity and Age-related Modulations of (A)synchrony Effects in a Spatial Stroop Task: An ERP and Behavioral Study - Leitão, José (2022)
Chronotype and time-of-day interactions are often manifest in differences between performance at times-of-day matching the individual's chronotype (on-peak) and off-peak performance. However, it is not clear which processing variables determine whether on- or off-peak benefits/costs will occur, nor how does ageing (young adult vs older adult) affect chronotype and time-of-day interactions. In this study, we use Event-Related Potentials to probe the processing underpinnings of these interactions at a millisecond time scale.